Medicinal and Aromatic Plants of Commercial Importance from Northeast India - Singh, Rambir (Indian Horticulture, 2024)
The Northeast India is part of Indo-Burma biodiversity hot-spot and is a home for large number of Medicinal and Aromatic plants (MAPs) of economic importance. The vast resource of MAPs in NER presents endless opportunities for establishing enterprises for addressing livelihood issue the growing demand for herbalbased environmentally friendly products. Considering the increase in demand of herbal products in recent times, NER can take advantage of production of raw/ semi processed material of highly valuable MAPs for building rural economy. This review summarizes the potential of some of the highly valuable MAPs to enhance rural economy in NER.